Rural Michigan Farmers' Health Concerns and Experiences: A Focus Group Study. (October 2021) - Wright, Nathan; Scherdt, Marylee; Aebersold, Michelle L.; McCullagh, Marjorie C.; Medvec, Barbara R.; Ellimoottil, Chad; Patel, Minal R.; Shapiro, Shoshana; Friese, Christopher R.
Objectives: Rural residents comprise approximately 15% of the United States population. They face challenges in accessing and using a health care system that is not structured to meet their unique needs. It is important to understand rural residents' perceptions of health and experiences interacting with the health care system to identify gaps in care. Methods: Our team conducted focus groups with members of the Michigan Farm Bureau during their 2019 Annual Meeting. Topics explored included resources to manage health, barriers to virtual health care services, and desired changes to localized healthcare delivery. Surveys were used to capture demographic and internet access information. Conclusion: Analysis included data from 2 focus groups (n = 14). Participants represented a wide age range and a variety of Michigan counties. The majority were full-time farm owners with most—93% (n = 13)—reporting they had access to the internet in their homes and 86% (n = 12) reporting that their cellphones had internet capabilities. Participants identified challenges and opportunities in 4 categories: formal health care; health and well-being supports; health insurance experiences; and virtual health care. Conclusion: The findings from this study provide a useful framework for developing interventions to address the specific needs of rural farming residents. Despite the expressed challenges in access and use of health care services and resources, participants remained hopeful that innovative approaches, such as virtual health platforms, can address existing gaps in care. The study findings should inform the design and evaluation of interventions to address rural health disparities.